1979
DOI: 10.1002/app.1979.070230908
|View full text |Cite
|
Sign up to set email alerts
|

Plasma polymerization of tetrafluoroethylene

Abstract: SynopsisThe plasma polymerization of C2F4 was carried out in both continuous wave and pulsed rf discharges to establish the effects of reaction conditions on the kinetics of polymer deposition and the polymer structure. ESCA spectra of the polymer show evidence for -CF3, -CF2, >CF-, and -CHZgroups. Under conditions favoring low deposition rates, the dominant functional group is -CF2-. At higher deposition rates the concentration of -CF2-groups is reduced and a more crosslinked polymer is produced. Both polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…Most of the applications are directed to fluorocarbon polymers because of the large chemical shifts in the binding energies of C(ls) electrons caused by fluorines bonded to carbon. As a result CF-, CF 2 , CF and tetrafunctional carbons can be distinguished (60,61,62,63,64). Knowing the relative electron line positions of the various groups, the C(ls) spectra can be deconvoluted and the group concentrations determined.…”
Section: Shen and Bellmentioning
confidence: 98%
“…Most of the applications are directed to fluorocarbon polymers because of the large chemical shifts in the binding energies of C(ls) electrons caused by fluorines bonded to carbon. As a result CF-, CF 2 , CF and tetrafunctional carbons can be distinguished (60,61,62,63,64). Knowing the relative electron line positions of the various groups, the C(ls) spectra can be deconvoluted and the group concentrations determined.…”
Section: Shen and Bellmentioning
confidence: 98%
“…At still higher values, decomposition of the polymer becomes important, yielding fluorine-poor polymerization products. Nakajima et al 17 used a similar framework to explain the behavior of the deposition rate in a TFE system. Polymeric products can also be formed on a substrate placed outside the plasma zone.…”
Section: Introductionmentioning
confidence: 98%
“…Some part of halogens in monomer were decomposed into ionic substances. Studies on the plasma polymerization of fluorocarbon were reported [4], [5], [6]. The work was performed for potential applications in the field of the coating industry as a surface protective coating and functional films.…”
Section: Characterization Of the Deposition Filmmentioning
confidence: 99%